An Introduction to Islam - Yasien Mohamed (International Institute of Islamic Thought, 1996)
David Waines, Islamic lecturer at Lancaster University, divides An Introduction to Islam into three parts. Part 1 deals with the Qur'an and the Sunnah in the formative period, and part 2 is devoted to Islamic teachings and practices, including separate chapters on Islamic law, theology, Sufism, and Shi'ism. The connecting thread in these first two parts is the ways in which Muslim scholars have explored "revelation and the experience of their Prophet, Muhammad" (p. 3). Part 3 treats Islam in the modern world, recounting the period over the last two centuries during which Muslims have been challenged by western hegemony and have sought to establish a modem sense of Islamic identity. This is a comprehensive, wide-ranging, and up-to-date treatment of Islamic history and culture. It is by no means the only recent introduction on Islam by a western scholar: Victor Danner's The Islamic Tradition: An Introduction (1988) deals with the Islamic intellectual and spiritual tradition within the context of other religious traditions. Frederick M. Dermy's An Introduction to Islam (1985) offers a comprehensive, simple account of Islam, and Annemarie Schinunels' Islam: An Introduction is a concise and ...